The Spanish cape mystery [large type] - Queen, Ellery (American Mystery Classics, 2023)
"A house party turns a millionaire's hacienda hideaway into a crime scene in this classic whodunnit from an Edgar Award-winning Grand Master. The Godfrey family is vacationing among the picturesque rocky cliffs of the North Atlantic seaboard, expecting peace, quiet, and, perhaps, a bit of golf or tennis. But one dusky evening in an isolated spot on the grounds of Spanish Cape, Rosa and her uncle David get into an argument about her secretive romance with one of their guests, the roguish John Marco, a handsome cad with a yellow roadster and no visible source of income. That's when a towering one-eyed man with a .38 revolver emerges from the twilight. When renowned sleuth Ellery Queen arrives the next day from New York City, looking forward to a summer getaway on the coast, he realizes his trip will be no walk on the beach. Rescuing Rosa, he discovers her captor mistook David for John and struck the former down instead. But Ellery has more work to do when Rosa's shady sweetheart is found stone dead and stark naked . . . aside from a black fedora and a theatrical-looking opera cloak. There are plenty of guests and members of the household who might have wanted John dead, but who did it--and what in the world happened to the victim's clothes? In this iconic series inspired by Sir Arthur Conan Doyle and praised by none other than Agatha Christie, carefully planted clues, logical deduction, and an atmospheric 1930s setting combine for an irresistibly enjoyable read for anyone who loves a murderous puzzle. Includes discussion guide questions for use in book clubs"--